2007
DOI: 10.1002/hyp.6879
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall patterns and critical values associated with landslides in Povoação County (São Miguel Island, Azores): relationships with the North Atlantic Oscillation

Abstract: Abstract:São Miguel Island (Azores) has been affected by hundreds of destructive landslide episodes in the last five centuries, triggered either by earthquakes, volcanic eruptions or rainfall episodes, which were responsible for many deaths and very important economic losses.Among the instability causes, meteorological factors are of primary importance on Povoação County, namely the high recurrence rate of calamitous rainfall triggering landslides. The most recent catastrophic episode took place on the 31st Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Usually failures occur on steep slopes ([30°) and are associated with cohesionless pyroclastic deposits or highly weathered lava basaltic (s.l.) lava flows (Marques 2013). Under these conditions, matric suction plays a crucial role in the shear strength, due to the effect of apparent cohesion, and contributes to maintaining slopes in physical equilibrium (Amaral et al 2009;Amaral 2010).…”
Section: Landslide Incidence In Mainland Portugal and São Miguel Islamentioning
confidence: 97%
See 1 more Smart Citation
“…Usually failures occur on steep slopes ([30°) and are associated with cohesionless pyroclastic deposits or highly weathered lava basaltic (s.l.) lava flows (Marques 2013). Under these conditions, matric suction plays a crucial role in the shear strength, due to the effect of apparent cohesion, and contributes to maintaining slopes in physical equilibrium (Amaral et al 2009;Amaral 2010).…”
Section: Landslide Incidence In Mainland Portugal and São Miguel Islamentioning
confidence: 97%
“…1b). The noncohesive materials (mostly pumice fall-out deposits) associated to the central volcanoes and the dominant steep slopes allow the existence of a very prominent landslide activity (Marques 2013).…”
Section: Landslide Incidence In Mainland Portugal and São Miguel Islamentioning
confidence: 99%
“…The island is characterized by a large variety of volcanic structures, including three active trachytic composite volcanoes with caldera (i.e., Sete Cidades, Fogo and Furnas; [85]). The highest elevation of the island (Pico da Vara, 1103 m) is localized between Povoação and Nordeste.…”
Section: Study Areamentioning
confidence: 99%
“…In a previous threshold study, a total of 19 different antecedent rainfall amounts ranging between 1 and 60 days were chosen and rainfall thresholds having short-term (7 days), medium-term (15 and 30 days) and long-term (60 days) durations were constructed (Garcia-Urquia and Axelsson 2015). The method used was the critical rainfall intensity, which had been applied successfully by Marques et al (2008) and Khan et al (2012) to assess landslide occurrence in Portugal and Bangladesh, respectively. Garcia-Urquia and Axelsson (2015) concluded that the predictive performance of the thresholds decreased with an increase in the threshold duration and therefore the threshold with the best performance in distinguishing between landslide and non-landslide days (hereafter known as LDs and NLDs, respectively) was the 7-day threshold.…”
Section: Overview Of Rainfall and Landslide Occurrence In Tegucigalpamentioning
confidence: 99%